Pre-Lacteal Feeding Practice in Hospitals of Lahore; A Multicenter Study - Amna Farooq, Ayesha Afzal, Mahek Zeeshan, Rabia Khalid, Muneeba Afzal, Fatima Kausar Nawaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Introduction of Pre-lacteal feeding soon after the baby is born is a common practice, and different predictors of PLFs have been reported worldwide. Mainly, people practice Pre-lacteal feeding to follow the religious beliefs or cultural traditions of their area. Objective: To describe the frequency, nature, reasons, and factors associated with Pre-lacteal feeding. Methods: 320 mothers and their neonates were studied from January 2022 to March 2022. Family and infant socioeconomic status, PLF classification, and PLF triggers were all recorded. Results: Nearly two-thirds of the infants were given prelacteal meals. Honey accounted for 59.3% of all PLFs. Conventional/historical reasons accounted for 80.2% of all PLF distributions in 2017. The independent predictors of PLF are urban residence, maternal education, age of mother and trend running in the family. Conclusion: Advantages of Pre-lacteal feeding along with breastfeeding should be studied more comprehensively to define a clear-cut relationship between the two.